LIFESTYLE, ATTITUDES AND HALAL LABELIZATION ON THE DECISION TO PURCHASE Y.O.U BRAND SKINCARE PRODUCTS. AT THE FULL RIVER WHATIE STORE - Yolla Ramadani; Hafizah _; Nurasiah _ (Jurnal Ilmu Pendidikan Ahlussunnah, 2023)
This study aims to determine: 1) Is there an influence of Lifestyle on purchasing decisions of Y.O.U Brand Skincare Products at the Whatie Store Store in Sungai Penuh and how much influence is partially? 2) Is there an influence of Attitude on purchasing decisions of Y.O.U Brand Skincare Products Whatie Store in Sungai Penuh and how big is the partial effect?3) Is there a partial effect of Halal Labeling on purchasing decisions for Skincare Products Brand Y.O.U Whatie Store Store in Sungai Penuh and how big is the effect partially?, 4) Is there an influence on Lifestyle, Attitudes and Labels Simultaneously Halal on the purchase decision of Y.O.U Brand Skincare Products Whatie Store in Sungai Penuh and how much influence does it have simultaneously? The research methodology used is descriptive qualitative and descriptive quantitative approaches. The research results are; 1) partially, there is an effect of Lifestyle on purchasing decisions for Skincare Products Brand Y.O.U Whatie Store Store in Sungai Penuh, 2) partially, there is an influence between Attitude towards purchasing decisions for Skincare Products Brand Y.O.U Whatie Store Store in Sungai Penuh, 3) . Partially, there is no effect of Halal Labeling on purchasing decisions of Y.O.U Brand Skincare Products at the Whatie Store Store in Sungai Penuh, 4) Simultaneously, there is simultaneous influence of Lifestyle, Attitudes and Halal Labels on purchasing decisions of Y.O.U Brand Skincare Products at Whatie Store Stores in Sungai Penuh.